La sintaxi de la conjugació en català - Viana, Amadeu (Caplletra. Revista Internacional de Filologia, 2015)
By "inflection" we usually understand morphological paradigms that constitue verbal casuistic. Syntax, as is normally understood, seems far from that. Instead of investigating the differences, I should concentrate on similarities. Perhaps "the sequence of tense" or the "consecutio temporum" would be better titles for this paper. It has been said that both inflection and syntax play an important role in the definition of sentences. The problem is who is going to give a definition of "consecutio temporum" today. Here I assume a model like Chomsky (1986) in order to explain the interaction between the Complementizer Phrase (as a mood marker) and the Inflection Phrase (both a morphological device and the head of the sentence). The starting point is represented by the work of T. Stowell (1981). I include also, finally, some comments on the kind of regularities we can find in the Inflection Phrase of Romance languages.